Profissão docente: uma análise de seu significado, tal como entendido nas revistas de educação mais consultadas no Brasil (1998-2008) - Pançardes, Bruna Casiraghi (2010)
The present work aims to perform a mapping on the Teaching Profession in articles published in five most consulted educational magazines, according to SciELO, during the years 1998 to 2008. This study is extremely necessary due to the vast literature on the subject, especially from the 90s. 43 articles with the terms profession, professionalism, professionalization, professionalism and professional development associated with the words: teacher, lecturer and teaching in issues subject, title and / or keywords were found. For analysis, items were divided into seven themes: 1) teaching work, 2) professional teaching, 3) Professional teaching staff, 4) Professional Development; 5) Teacher Education, 6) knowledge and practices and 7) conditions of work. It was found that: most items are essays made by authors in the field of Teacher Training, a large number of articles is aimed at the analysis of the changes proposed by the Law of Directives and Bases of Education from 1996 and the Guidelines for the course of Pedagogy, teaching profession is multifaceted, and yet, there is lack of consensus among authors on the aspects and conditions of the teaching profession. We highlight the importance of the role of the teacher in the educational process as one of the main characters, along the students and finding that the factors involved in the profession affect the professional, the teacher and also his relationship with the students